2017
DOI: 10.1108/compel-02-2016-0050
|View full text |Cite
|
Sign up to set email alerts
|

Novel design topology for low leakage field and vibration motor

Abstract: Purpose: The purpose of the paper is to introduce a novel design topology for an electric motor, which has essentially none of the normal sources of magnetic alternating force. Design/methodology/approach: Two-dimensional (2D) and three-dimensional (3D) finite element methods are used to analyze the electromagnetic performance of the proposed machine. 3D integral equations are used to calculate the scalar potentials. Detailed manufacturing process and the results of the testing are presented. Findings The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Thus, improvements in lightweight constructions and material savings are limited for designs. This highlights the significance of novel machine designs, such as those shown in Salon and Ergene (2017), Jedryczka et al (2016), Liu et al (2016), Vukoti c andMiljavec, (2016) and Guo et al (2016). A patented air gap winding, as presented in Kasper et al (2015), uses a magnetic circuit with very thin iron cores without slots, in both rotor and stator.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, improvements in lightweight constructions and material savings are limited for designs. This highlights the significance of novel machine designs, such as those shown in Salon and Ergene (2017), Jedryczka et al (2016), Liu et al (2016), Vukoti c andMiljavec, (2016) and Guo et al (2016). A patented air gap winding, as presented in Kasper et al (2015), uses a magnetic circuit with very thin iron cores without slots, in both rotor and stator.…”
Section: Introductionmentioning
confidence: 99%
“…Vibration analysis, ultrasound analysis, stator current frequency processing, external search coil next to the motor stator and visual analysis for shaft faults can simply identify the cause(s) of failure and eccentricity from the motor's outer region. In this regard, very comprehensive studies addressing such problems can be found (Çıra, 2018; Lin et al , 2018b; Zhang et al , 2018; Lin et al , 2018a; McCloskey et al , 2018; Kim et al , 2016; Li et al , 2016; Lin and Zuo, 2016; Le Besnerais et al , 2016; He et al , 2020; Wang et al , 2021; Salon and Ergene, 2017).…”
Section: Introductionmentioning
confidence: 99%